2016
DOI: 10.14704/nq.2016.14.1.911
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Wave Information of Life Revealed: An Algorithm for Electromagnetic Frequencies that Create Stability of Biological Order, With Implications for Brain Function and Consciousness

Abstract: We propose a hypothesis of a mathematical algorithm for coherent quantum frequencies, that may create stability of biological order. The concept is based on an extensive literature survey, comprising 175 articles from 1950 to 2015, dealing with effects of electromagnetic radiation on in vitro and in vivo life systems, indicating that typical discrete coherent frequencies of electromagnetic waves are able to stabilize cells, whereas others cause a clear destabilization. We find support for the hypothesis of H. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 70 publications
1
65
0
1
Order By: Relevance
“…Using the proposed algorithmic frequencies of Meijer and Geesink, 2016, it can be concluded that there is a good match with 27 randomly selected data of Ritz including 18 measured data of Chladni. The mean partial gap between de algorithmic frequencies and the Ritz/Chladni data is very close and amounts 0.91% (appendix 1 and Figure 4).…”
Section: Data Of Chladni Ritz and Calculations Of Chen May Confirm Tmentioning
confidence: 89%
See 4 more Smart Citations
“…Using the proposed algorithmic frequencies of Meijer and Geesink, 2016, it can be concluded that there is a good match with 27 randomly selected data of Ritz including 18 measured data of Chladni. The mean partial gap between de algorithmic frequencies and the Ritz/Chladni data is very close and amounts 0.91% (appendix 1 and Figure 4).…”
Section: Data Of Chladni Ritz and Calculations Of Chen May Confirm Tmentioning
confidence: 89%
“…Geesink (2006), discovered that silicate minerals, which may act as a catalyst to synthesize RNA-like molecules, emit coherent electromagnetic patterns at discrete light, infrared and far infrared frequencies. These frequency patterns, based on quantum transitions obey to frequency ratios of 1:2, and approximate partials of 2:3 (Geesink and Meijer, 2016). Due to the fact that these minerals are a potential candidate to synthesize RNA and may have been instrumental in the initiation of first life at the edge of pre-biotic biological evolution, we decided to carry out a broad literature study to verify whether these frequencies are also found in biological cell studies.…”
Section: Patterns Of the Quantum Wave Information Influencing Life Smentioning
confidence: 99%
See 3 more Smart Citations